Avaliação pulmonar de nascidos prematuros durante a adolescência por meio da técnica de oscilações forçadas - Accorsi, Bruna Freire (2020)
Introduction: Annually, approximately 15 million children are born premature (<37 weeks of gestational age). Of these, about 1 million die in the first month of life due to respiratory complications. Technological advances in neonatal intensive care allow na increase in the survival of babies born prematurely and many reach adulthood. However, respiratory morbidity remains a frequent complication. Monitoring a pulmonary function of these patients in medium and long terms seems to have relevance for monitoring their respiratory development. This monitoring can be performed through tests such as spirometry and forced oscillation technique (FOT), which measure the impedance of the respiratory system (Zrs) in the spectral and intra-breath phases. The Zrs of adolescents born prematurely is still little known. Objectives: To describe the Zrs of adolescents born prematurely and to compare it with controls born at term. Methodology: 51 adolescents of both sexes took part in the study, which were divided into two groups: 35 participants in the premature group and 16 in the control group (participants born at term). To compose the group of premature infants, a sample of a cohort of patients born prematurely at the São Lucas Hospital of the Pontifical Catholic University of Rio Grande do Sul (HSL-PUCRS), Porto Alegre/RS, Brazil, started to investigate the effects of prematurity and perinatal events in lung development. These participants were recruited via telephone contact. Controls were recruited from pediatric outpatient clinics at HSL-PUCRS, for convenience. Participants in the preterm group were, at the time of collection, aged between 11 years and 11 months and 13 years and 9 months. The controls, from 12 years to 13 years and 9 months. Pulmonary assessment was performed using spirometry and FOT, according to the recommendations of the American Thoracic Society (ATS) / European Respiratory Society (ERS). Results: Spirometry and spectral oscillometry did not detect differences in lung function between adolescents born prematurely and controls. The comparison of the intra-breath oscillometry values between the groups showed significant differences in the variables R (P=0.003), XeI (P=0.027) and X (P=0.027). Conclusions: Intra-breath oscillometry was able to detect significant differences between groups in three variables, suggesting the persistence of abnormalities in Zrs in adolescents born prematurely, and also that the intra-breath phase may be more sensitive than spectral oscillometry. However, studies with larger samples are required to validate these findings and to explore the long-term association between gestational age (GA) and Zrs.